Global distribution and readiness status of artificial intelligence application on mobility projects. (March 2023) - Pandyaswargo, Andante Hadi; Maghfiroh, Meilinda Fitriani Nur; Onoda, Hiroshi
Abstract: The mobility sector is experiencing a global transition towards cleaner and more sustainable technologies. Many mobility projects are developing artificial intelligence (AI) technologies to improve the operational efficiency of mobility, such as charging system optimization for electric vehicles (EVs), autonomous driving, and traffic controls. This study presents such projects' global distribution by showing a geographic information system (GIS)-generated map and analyzes the readiness level of those technologies by employing the Japanese Technology Readiness Assessment (J-TRA) methodology. The results show that most projects are located in Europe. Among the analyzed AI uses, the smart parking system and lane tracing assistance technologies have the highest level of readiness. Further training of AI to be fully compatible with the real operating environments and updates of traffic policies are necessary to allow advancement of the technology readiness of the rest of AI mobility technologies types.